Moores Beweis, Wahrnehmung und Skeptizismus - Dierig, Simon (Grazer philosophische Studien, 2017)
Two major arguments have been advanced for the claim that there is a transmission failure in G.E. Moore’s famous proof of an external world. The first argument, due to Crispin Wright, is based on an epistemological doctrine now known as ‘conservatism’. Proponents of the second argument, like Nicholas Silins, invoke probabilistic considerations, most important among them Bayes’ theorem. The aim of this essay is to defend Moore’s proof against these two arguments. It is shown, first, that Wright’s argument founders because one of its premises, viz., conservatism, invites scepticism and must therefore be rejected. Then the probabilistic argument is challenged, not because its formal part is dubious, but rather on the grounds that it incorporates an unconvincing philosophical claim as an implicit premise. Finally, the two most promising objections to dogmatism—the negation of conservatism—are repudiated
Gesehen am 07.04.2021